Influence of sowing dates and cutting management on productivity and profitability of dual purpose barley (Hordeum vulgare L.) in Indo- Gangetic Plains of India - Dhillon, Balwinder Singh; Uppal, R S (Journal of Cereal Research, 2019)
A study was carried out during winter season of 2015-16 and 2016-17 to find out optimum time of sowing and suitable cutting management for higher growth, productivity and economics of dual purpose barley (Hordeum vulgare L.). Growth attributes i.e. plant height and dry matter of October 15 sown crop were highest when fodder cut was taken at 50 days after sowing (DAS). Significantly higher productivity (fodder, grain and biological yields) of barley was observed in early sowing (October 15). Control and cut at 50 DAS treatments produced statistically similar grain and biological yields and it can be delayed up to 60 DAS to get more production of green fodder (40.5 to 41.8%) than at 50 DAS but at the cost of 20.6-22.7% reduction in grain yield. Crop sown on October 15 with fodder cut at 60 DAS + 25% additional N application (15 kg N ha- 1) after fodder cut resulted in significantly higher net return (Rs 82,863) vis-a-vis benefit cost ratio (2.88).